Physical Fitness after Anterior Cruciate Ligament Reconstruction: Influence of Graft, Age, and Sex - Robert Csapo; Helmut Pointner; Christian Hoser; Peter Gföller; Christian Raschner; Christian Fink (MDPI AG, 2020)
Functional tests are used to facilitate return-to-sports decisions after anterior cruciate ligament reconstruction (ACLR). This study presents comprehensive physical fitness test data acquired in highly active patients within the first year after ACLR, for comparison between different grafts, age groups, and sexes. The outcomes from a specific seven-item test battery and isokinetic strength test data were extracted from a patient database. Results were compared to normative data from age- and sex-matched controls and between subgroups of patients. A total of 245 patients (94 women, 23.8 ± 8.4 years, pre-injury Tegner 7.4 ± 1.6) were tested 185 ± 44 days after surgery. In 116 patients (47.3%), one or more test results were classified as “poor” or “very poor” after comparison with normative data, with failures being most frequent during single-leg squat jump and plyometric strength tests. Test failures were more prevalent in adults than in adolescents <19 years (61.4%−62.2% vs. 24.5%, p < 0.001) and in men (61.6% vs. 24.5%, p < 0.001), but no differences were found between grafts. Isokinetic knee extensor strength was lower by 24.1% on the injured side. Six months after ACLR, nearly 50% of highly active patients presented with strength and functional fitness deficits. These deficits are particularly prevalent in older patients and men.